2008
DOI: 10.1063/1.2945895
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dynamics of H2, D2, and HD in the small dodecahedral cage of clathrate hydrate: Evaluating H2-water nanocage interaction potentials by comparison of theory with inelastic neutron scattering experiments

Abstract: We have performed rigorous quantum five-dimensional (5D) calculations and analysis of the translation-rotation (T-R) energy levels of one H(2), D(2), and HD molecule inside the small dodecahedral (H(2)O)(20) cage of the structure II clathrate hydrate, which was treated as rigid. The H(2)- cage intermolecular potential energy surface (PES) used previously in the molecular dynamics simulations of the hydrogen hydrates [Alavi et al., J. Chem. Phys. 123, 024507 (2005)] was employed. This PES, denoted here as SPC/E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
137
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(156 citation statements)
references
References 48 publications
19
137
0
Order By: Relevance
“…This uniquely high degree of realism and detail in simulating the INS spectra is not achievable by the approaches in the literature. It is made possible by our ability to compute accurately the fully coupled quantum 5D T-R energy levels and wave functions of the entrapped molecule on the 5D intermolecular PES 11,12,15,16 and, as shown here, use them as input for calculating the spectra.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This uniquely high degree of realism and detail in simulating the INS spectra is not achievable by the approaches in the literature. It is made possible by our ability to compute accurately the fully coupled quantum 5D T-R energy levels and wave functions of the entrapped molecule on the 5D intermolecular PES 11,12,15,16 and, as shown here, use them as input for calculating the spectra.…”
mentioning
confidence: 99%
“…12 . At 20 K, the temperature of the experiment, only the lowest rotational states J = 0, 1 are populated, and therefore are the only initial states considered in the calculations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bačić et al have studied these effects in much detail for hydrogen-containing clathrates [48][49][50][51][52][53][54], including explicit path-integral MD simulation [54]; based on these studies, it should be stressed that the classical MD results at 100 K and below reported in the present work needs to be interpreted with some caution due to the limitations of classical MD to describe accurately H 2 motion at low temperatures.…”
Section: Methodsologymentioning
confidence: 90%
“…Our approach to the rigorous calculation of the coupled five-dimensional T-R energy levels and wave functions of a hydrogen molecule inside fullerenes, applied in this study to HD@C 60 , has evolved in our group over a number of years, in the course of the theoretical investigations of the quantum T-R dynamics of H 2 and its isotopologues entrapped in the cages of clathrate hydrates [19][20][21], fullerenes C 60 and C 70 [2,5], and an open-cage derivative of C 60 (ATOCF) [22]. A detailed description of the quantum five-dimensional methodology is available in [18], and therefore only the salient features are given here.…”
Section: Theorymentioning
confidence: 99%